Investigation of Boron Concentrations in the Water of Rivers and Wells in Northern Regions of Thi-Qar Province Using SSNTDs Technique - Ihsan Razzaq Shia; Abbas Abd Sweaf (University of Thi-Qar Journal of Science, 2024)
The Iraqi environment is polluted, especially in the southern region, due to human domestic activities, such as sewage water containing boron due to washing powders that boron participates in producing, which are not connected to sewage networks and are poured into the river water, in addition to industrial facilities and farmers’ use of fertilizers that contain boron, which also contributed effectively to increasing the concentration of boron, as the work areas work specifically to monitor minerals in the water sample, which is essential to controlling the human environment in the north of Thi-Qar Governorate. In this study, 31 colors of Nahr Bar water were collected, and boron concentrations were measured using SSNTDs CR39 technology and the 241Am-Be neutron beam station. Selected water samples were taken from different waters and from water sources and the Euphrates River in various residential, agricultural and industrial sites. Boron concentrations in well water from 1.94 to 3.63 mg/L, while boron levels in river water ranged from 1.85 to 2.34 mg/L. Boron levels in well water were higher than those in river water samples. Boron concentrations in agricultural sites were higher than in industrial and residential sites. Boron levels in most water samples were below the required levels set by the US Environmental Protection Agency and the World Health Organization. However, monitoring water to prevent contamination from affecting the human chain is important.